Perspectives on high-quality interpersonal care among people obtaining abortions in Argentina - Chiara Bercu; Sofía Filippa; Ana Maria Ramirez; Anna Katz; Belén Grosso; Ruth Zurbriggen; Sandra Vázquez; Sarah E. Baum (BMC, 2022)
Plain language summary Little is known about how people who have abortions perceive the quality of the care they receive and what aspects of interpersonal interactions with providers matter to them. This qualitative study aimed to understand preferences of  people who had abortions at both a reproductive health clinic and with an accompaniment group in Argentina. We interviewed 24 people who obtained abortion care in Buenos Aires and Neuquén, Argentina. We asked them about their preferences for and experiences of abortion care. Then we analyzed the interviews, specifically assessing aspects of interpersonal care based on quality of care frameworks from the literature. Participants described high-quality abortion care as feeling acompañamiento and contención from their providers-terms that imply receiving kind, caring, compassionate and emotionally supportive care throughout their abortions. They described four key elements of interpersonal interactions: attentive communication from providers and accompaniers, clear and understandable information provision, non-judgmental support, and individualized options for pain management. In conclusion, people obtaining abortions in two distinct models of care in Argentina consistently identified receiving compassionate and supportive care throughout an abortion as a key aspect of care. The findings have implications for incorporating people's perspectives in the development of care guidelines, training of providers, and monitoring and improving of services. This is particularly important as the government of Argentina prepares to expand legal access to abortion.